Mechanisms underlying the involvement of peritoneal macrophages in the pathogenesis and novel therapeutic strategies for dialysis-induced peritoneal fibrosis - Wang, Yangwei; Zhang, Yixian; Ma, Mingqi; Zhuang, Xiaohua; Lu, Yue; Miao, Lining; Lu, Xuehong; Cui, Yingchun; Cui, Wenpeng (Frontiers in Immunology, 2024)
Long-term exposure of the peritoneum to peritoneal dialysate results in pathophysiological changes in the anatomical organization of the peritoneum and progressive development of peritoneal fibrosis. This leads to a decline in peritoneal function and ultrafiltration failure, ultimately necessitating the discontinuation of peritoneal dialysis, severely limiting the potential for long-term maintenance. Additionally, encapsulating peritoneal sclerosis, a serious consequence of peritoneal fibrosis, resulting in patients discontinuing PD and significant mortality. The causes and mechanisms underlying peritoneal fibrosis in patients undergoing peritoneal dialysis remain unknown, with no definitive treatment available. However, abnormal activation of the immune system appears to be involved in altering the structure of the peritoneum and promoting fibrotic changes. Macrophage infiltration and polarization are key contributors to pathological injury within the peritoneum, showing a strong correlation with the epithelial-to-mesenchymal transition of mesothelial cells and driving the process of fibrosis. This article discusses the role and mechanisms underlying macrophage activation-induced peritoneal fibrosis resulting from PD by analyzing relevant literature from the past decade and provides an overview of recent therapeutic approaches targeting macrophages to treat this condition.